Variability in a collection of coriander (Coriandrum sativum L.) germplasm - YADAV, R K (Journal of Spices and Aromatic Crops, 1999)
Surveys were conducted for collection of coriander (Coriandrum sativum L.) germplasm from Jabalpur (Madhya Pradesh, India) during 1996-97. The collections were sown at Regional Agricultural Research Station, Raigarh, Madhya Pradesh for evaluation and some of their morphological attributes are presented in Table 1.